STRATEGI PEMBELAJARAN AKTIF UNTUK MENINGKATKAN KEMAMPUAN MENEMUKAN IDE POKOK PADA SISWA KELAS IV SD - Yeni Rahmawati; Daroe Iswatiningsih; Binti Solikah; Riza Ummaroch; Fatmawati H.A. Zakariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of active learning strategies in improving the ability of fourth-grade students at SD Muhammadiyah Terpadu Ponorogo to identify the main idea of a text. The research subjects consisted of 28 fourth-grade students. The strategies applied included the use of computer-based media, interactive questioning, and group discussion. This study employed a descriptive qualitative approach, focusing on the learning process and students’ responses throughout the activities. Data were collected through participatory observation, documentation, and teacher reflection. The data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the active learning strategies computer-based media, interactive questioning, and group discussion successfully enhanced students’ enthusiasm and engagement during the learning process. The use of computer-based media captured students’ attention and made reading activities more enjoyable. Interactive questioning helped strengthen students’ comprehension of the text, while group discussions provided opportunities for collaboration, idea sharing, and practicing main-idea identification more accurately. Students responded very positively to the strategies, as reflected in their increased participation, motivation, and confidence during reading activities. The study concludes that the implementation of active learning strategies can serve as an effective alternative for improving the quality of reading instruction in elementary schools.